2020
DOI: 10.5194/cp-16-885-2020
|View full text |Cite
|
Sign up to set email alerts
|

A proxy modelling approach to assess the potential of extracting ENSO signal from tropical Pacific planktonic foraminifera

Abstract: Abstract. A complete understanding of past El Niño–Southern Oscillation (ENSO) fluctuations is important for the future predictions of regional climate using climate models. One approach to reconstructing past ENSO dynamics uses planktonic foraminifera as recorders of past climate to assess past spatio-temporal changes in upper ocean conditions. In this paper, we utilise a model of planktonic foraminifera populations, Foraminifera as Modelled Entities (FAME), to forward model the potential monthly average δ18O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 144 publications
(246 reference statements)
0
12
0
Order By: Relevance
“…We furthermore have shown in our best-case study that a species' abundance response to SST can inherently bias IFA-derived reconstructions of past SST variance. We propose that the coupling of a single foraminifera sediment model approach to foraminiferal ecological models (Lombard et al, 2011;Metcalfe et al, 2020;Roche et al, 2018) could further help to constrain the total uncertainty associated with IFA-derived SST reconstructions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We furthermore have shown in our best-case study that a species' abundance response to SST can inherently bias IFA-derived reconstructions of past SST variance. We propose that the coupling of a single foraminifera sediment model approach to foraminiferal ecological models (Lombard et al, 2011;Metcalfe et al, 2020;Roche et al, 2018) could further help to constrain the total uncertainty associated with IFA-derived SST reconstructions.…”
Section: Resultsmentioning
confidence: 99%
“…4). The equivalent figures for the 5 cm ka -1 and 10 cm ka -1 scenarios, which may more be representative best-case values for the open ocean areas of the Pacific (Metcalfe et al, 2020), can be found in the supplement.…”
Section: Downcore Discrete-depth Ifa Standard Deviationmentioning
confidence: 99%
See 1 more Smart Citation
“…the downcore, discrete-depth record) is itself modified by bioturbation (Lougheed 2020), and therefore does not reflect the original species abundance signal in the time domain. Species abundance in the time domain, which is called for in the calibration protocol outlined here, could be based on an estimates from, e.g., a transient palaeoclimate model run linked to an ecological model (Lombard et al 2011;Morard et al 2013;Roche et al 2018;Metcalfe et al 2020), although estimating relative temporal abundance of a…”
Section: Advice For Determining Prior Valuesmentioning
confidence: 99%
“…Regarding issues in the water domain, it is possible that a foraminifera species may not continually inhabit a single surface water location or water depth, thus giving a non-continuous record of SST, which can have consequences for, e.g., ENSO reconstructions (Metcalfe et al, 2020). Secondly, a species' foraminiferal abundance through time is not constant and can be influenced by SST itself, which may bias IFA-derived SST distribution reconstructions, which is especially relevant in the case of ENSO, which itself influences SST.…”
Section: Introductionmentioning
confidence: 99%